![image](https://tex.z-dn.net/?f=log_%7B2%7D%283-2x%29-log_%7B2%5E%7B-3%7D%7D%283-2x%29%3E+%5Cfrac%7B4%7D%7B3%7D+)
\frac{4}{3} " alt="log_{2}(3-2x)-log_{2^{-3}}(3-2x)> \frac{4}{3} " align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=log_%7B2%7D%283-2x%29%2Blog_%7B2%7D%283-2x%29%5E%7B+%5Cfrac%7B1%7D%7B3%7D%7D+%3E+%5Cfrac%7B4%7D%7B3%7D+)
\frac{4}{3} " alt="log_{2}(3-2x)+log_{2}(3-2x)^{ \frac{1}{3}} > \frac{4}{3} " align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=log_%7B2%7D%283-2x%29%5E%7B+%5Cfrac%7B4%7D%7B3%7D%7D+%3E+%5Cfrac%7B4%7D%7B3%7D)
\frac{4}{3}" alt="log_{2}(3-2x)^{ \frac{4}{3}} > \frac{4}{3}" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D%2Alog_%7B2%7D%283-2x%29%3E%5Cfrac%7B4%7D%7B3%7D)
\frac{4}{3}" alt="\frac{4}{3}*log_{2}(3-2x)>\frac{4}{3}" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=log_%7B2%7D%283-2x%29%3E1)
1" alt="log_{2}(3-2x)>1" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=3-2x%3E2)
2" alt="3-2x>2" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=-2x%3E2-3)
2-3" alt="-2x>2-3" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=-2x%3E-1)
-1" alt="-2x>-1" align="absmiddle" class="latex-formula">
Ответ: x∈(-бесконечность; 0.5)